Seed priming and abiotic stress tolerance in carrot: Unraveling the mechanisms of improved germination. - Marcin Nowicki; Marzena Nowakowska; Katarzyna Nowak; Wojciech Szczechura; Piotr Kaminski (PLoS ONE)
Climate change necessitates the development of improved crops capable of withstanding future weather patterns. Carrots (Daucus carota L.), a crucial vegetable crop of global importance, face unique challenges in seed germination and seedling development due to their complex pollination biology and outcrossing reproduction mode with severe inbreeding depression if selfed. This study investigated the effects of salinity and drought stress on carrot seed germination and seedling development, with focus on the roles of seed priming, cellular processes inhibitors, and biochemical responses. Seed priming agents were hypothesized to enhance stress tolerance by modulating specific cellular and biochemical pathways, such as improving osmotic balance, enhancing antioxidant defense mechanisms, and activating stress-responsive genes. We also hypothesized that specific cellular processes and biochemical pathways influence the germination and early seedling growth of carrot seeds under salinity or drought stress. To test that hypothesis, we evaluated the effects of seed priming with various agents (e.g., water, NaCl, PEG, GA3) on germination rates and seedling vigor. Additionally, we investigated the impact of inhibitors (actinomycin D-inhibitor of transcription, cycloheximide-inhibitor of translation, hydroxyurea-inhibitor of DNA synthesis, cytochalasin-inhibitor of actin polymerization) on seed germination under stress conditions. Biochemical responses, including reactive oxygen species (ROS) levels and antioxidant enzyme activities, were analyzed to identify genotype-specific adaptations indicative of stress tolerance. Our results revealed significant variability in germination rates and seedling growth among the studied carrot experimental lines and commercial cultivars under salinity or drought stress Seed priming enhanced germination and seedling vigor by up to 35% under salinity stress and 28% under drought stress, with notable differences observed across the priming agents. The application of inhibitors highlighted the involvement of specific cellular processes in regulation of seed germination under stress. For instance, actinomycin D reduced germination by 40% under salinity stress. Biochemical analyses indicated genotype-specific responses, with variations in ROS levels and antioxidant enzyme activities such as superoxide dismutase and peroxidase. ROS levels increased by 50% under drought stress, whereas antioxidant enzyme activities varied substantially among genotypes. These findings underscored the importance of genotype-specific adaptations in conferring salinity or drought tolerance in carrot seedlings. Future research integrating omics approaches (e.g., transcriptomics, proteomics, metabolomics) will provide deeper insights into the molecular mechanisms that regulate stress tolerance, to aid in the development of more resilient carrot varieties suitable for cultivation under adverse environmental conditions.